Effect of ras-blockers and no-cycle metabolites on the renal functions of rats exposed to thyroxine injections - Dolomatov, S. I.; Sataieva, T. P. (Journal of Education, Health and Sport, 2014)
Dolomatov S. I., Sataieva T. P. Effect of ras-blockers and no-cycle metabolites on the renal functions of rats exposed to thyroxine injections. Journal of Education, Health and Sport. 2015;5(1):41-55. ISSN 2391-8306. DOI: 10.5281/zenodo.13902 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A41-55 https://pbn.nauka.gov.pl/works/522594 http://dx.doi.org/10.5281/zenodo.13902 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2014. Revised 05.10.2014. Accepted: 12.01.2015. EFFECT OF RAS-BLOCKERS AND NO-CYCLE METABOLITES ON THE RENAL FUNCTIONS OF RATS EXPOSED TO THYROXINE INJECTIONS S. I. Dolomatov, T. P. Sataieva Crimea State Medical University Simferopol, Russian Federation Corresponding author: Sergei Dolomatov E-mail: path888d@yandex.ru Abstract Objective. Evaluating the role of RAS and NO-dependent pathogenic mechanisms of formation of renal dysfunction in disorders of the thyroid status. Methods. First 2 groups of experimental white male outbredrats was administered thyroxine (T4) in a dose of 50 g / 100 g per body weight injected intraperitoneally on 1% starch gel base once or during 7 days. In addition, rats were administered non-selective NO-synthase inhibitor Nω-NLA. Those rats were exposed to single administration of the combined T4 (intraperitoneally, 50mg/100g body weight in 24 hours before water loading) and Nω-NLA (intraperitoneally 1 mg / 100 g body weight 30 min before water loading). As a comparison we studied a group of animals received only an equivalent dose only or T4 Nω-NLA only 1 mg / 100 g body weight in 30 min before water loading. After 7-days. of T4 administration the same rats received water solution of losartan (10 mg / l) or water solution of captopril (20 mg / l) for 24 hours after the last administration of T4. Another group of rats was treated with T4 for 7 days and afterwards was administered L-arginine in a dose 2 mg / 100 g bw per day or water solution (20 mg / l) of sodium nitrite. Rats in the control group for 7 days. was administered intragastrically gel containing no T4. Kidney function was studied in 24h after administration of T4 in terms of water 5% loading on kidneys. Results. It was found out that administaration of RAS-blockers increases creatinine clearance value after either a single or prolonged administration of T4 in rats. However, decreased renal excretion of endogenous nitrates and protein as well as prevented retention of endogenous nitrite was registered in rats only after administration of losartan after 7 days of T4 administration. Prolonged administration of T4 to the rats was accompanied by weakened renal effects of NO and activated the arginine dependent pathway of NO synthesis into the nitrite reduction, evidenced by the increase of endogenous nitrite level in blood plasma of rats treated with T4 continuously along with no pronounced corrective effect of exogenous arginine in hyperthyroid animals and elevated creatinine clearance under the influence of exogenous sodium nitrite in the hyperthyroid animals. Conclusion. Discovered effects of RAS blockers allow us to recommend this pharmacological agents as an effective way to slow down the progression of renal dysfunction inthyroid pathlogy. Keywords: rat, hyperthyroidism, renal function, RAS- inhibitors, nitrites, nitrates.